A Pipeline for Automated Supervised Tuning of LLMs - Fernandes, Diego D.; Silva, Thalyson G. N.; Santos, Rafael S.; Marajo, Felipe G.; Rocha, Cleilton L.; Barros, Ana Luiza B. P.; Campos, Gustavo A. L. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2025)
The increasing complexity of language models and the growing diversity of Natural Language Processing (NLP) tasks have emphasized the need for automated and efficient tuning processes. But, while advances in Automated Machine Learning (AutoML) and parameter-efficient fine-tuning (PEFT) techniques have been made, there is still a lack of structured workflows adapted to the specific challenges of Large Language Models (LLM). This work proposes a conceptual, modular Automated Large Language Model (AutoLLM) pipeline that integrates both full and lightweight supervised fine-tuning strategies under a unified optimization framework. The pipeline leverages simulation-based search methods, particularly bioinspired algorithms such as Genetic Algorithms (GA), to automate hyperparameter tuning in supervised LLM adaptation. Preliminary experiments were conducted using Quantized Low-Rank Adaptation (QLoRA) for lightweight fine-tuning on the summarization task. The results illustrate the adaptability and efficiency of the approach in optimizing LLMs for one downstream application while maintaining computational feasibility. The proposed pipeline offers a structured foundation for advancing AutoML in the context of language model tuning.